2021
DOI: 10.1080/21670811.2021.1957967
|View full text |Cite
|
Sign up to set email alerts
|

News Avoidance during the Covid-19 Crisis: Understanding Information Overload

Abstract: This study investigates the degree of news avoidance during the first months of the Covid-19 pandemic in the Netherlands. Based on two panel surveys conducted in the period April-June 2020, this study shows that the increased presence of this behavior, can be explained by negative emotions and feelings the news causes by citizens. Moreover, news avoidance indeed has a positive effect on perceived well-being. These findings point to an acting balance for individual news consumers. In a pandemic such as Covid-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 34 publications
3
58
0
1
Order By: Relevance
“…Both previous research as well as our participants highlighted how news often presents news by evoking negative emotions (Aslam et al 2020;Nguyen et al 2021). While studies that predate the pandemic foresaw an important role for news media in times of crisis, for some users, the news environment during the coronavirus pandemic appears to have brought with it emotional and mental strain (de Bruin et al 2021;Nguyen et al 2021). In line with Skovsgaard and Andersen (2020), solutions to intentional news avoidance practices are found in the selection and presentation of news.…”
Section: Discussion: News Avoidance As a Fluid Reconfiguration Of Repertoiresmentioning
confidence: 99%
See 1 more Smart Citation
“…Both previous research as well as our participants highlighted how news often presents news by evoking negative emotions (Aslam et al 2020;Nguyen et al 2021). While studies that predate the pandemic foresaw an important role for news media in times of crisis, for some users, the news environment during the coronavirus pandemic appears to have brought with it emotional and mental strain (de Bruin et al 2021;Nguyen et al 2021). In line with Skovsgaard and Andersen (2020), solutions to intentional news avoidance practices are found in the selection and presentation of news.…”
Section: Discussion: News Avoidance As a Fluid Reconfiguration Of Repertoiresmentioning
confidence: 99%
“…Again, these users have sought refuge in news avoidance practices in order to shield themselves from further mental strain (Nguyen et al 2021). While previous studies have already shown a relation between certain news and negative emotions or mental well-being (Boukes and Vliegenthart 2017;de Bruin et al 2021; Ytre-Arne and Moe 2021), this is especially problematic during a global health crisis where news users are already in a more vulnerable position. While we agree that habitual news avoidance might thus highlight important sociodemographic and structural fault lines in news consumption practices, exploring situational bouts of news avoidance might provide important insights into how users experienced news and enacted news avoidance practices during the pandemic.…”
Section: Large-scale News Events As a Context For The Exploration Of Situational News Avoidancementioning
confidence: 94%
“…Exposure to the most important news is of particular importance in the context of information overload (Zarcadoolas et al 2009), which is one of the characteristics of the COVID-19 infodemic. Empirical research has found that as many as 60% of the population felt overloaded with information at the beginning of the coronavirus crisis (de Bruin et al 2021).…”
Section: Gatekeeping As Editorial Oversight In the Context Of The Cov...mentioning
confidence: 99%
“…As awareness around doomscrolling grows, users might become wary of news outlets and social media accounts that post disproportionately negative content. Individuals who experience negative outcomes from doomscrolling may then develop news avoidance techniques to protect their wellbeing, a finding echoed by recent surveys on COVID-19 information overload, well-being, and avoidance (de Bruin et al, 2021;Jain, 2021).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%